Evaluating Basic English Language Courses in the Foundation Programme at an Educational Institute in the United Arab Emirates: Instructor and Student Perspectives - ABU SHUNNAR, BASHAR (2018)
"The current research study was designed with the purpose of evaluating the Basic English Language Courses (BELC), in the Foundation Programme (FP) at an educational institute in the United Arab Emirates (UAE). Motivated by the apparent shortfall of requisite English language skills of UAE engineering and business graduates, when it comes to securing employment, the current study investigated the suitability of the English courses, and teaching methodologies. This was accomplished by eliciting the opinions of the programme participants regarding the programme’s quality. These outcomes subsequently formed the basis upon which programme improvements were suggested. The BELC comprises three courses: 1) reading; 2) writing; and 3) conversation. Students in their first semester of institute enrolment must undertake these BELC courses, in order to enhance their English language ability. Due to the investigatory nature of the current study, and its context-specificity, the naturalistic-interpretive approach, along with the social constructivist approach, were employed to generate the epistemological stance, which focuses mainly on human interactions and environments. Adopting such a paradigm will support comprehension and interpretation, of participant experiences in the BELC and FP. The current study’s research design employed a sequential mixed methods case study, analysing and integrating both quantitative and qualitative data. In addition, it utilized an Eclectic Approach as an evaluative model for the purpose of better understanding the research problem. Participants were composed of three lecturers, who were teaching the BELC courses, and 55 students in their first year at the FP. The current study made use of both qualitative and quantitative instruments of data collection but greater focus was given to qualitative methods because of the social constructivist stance adopted. The data were collected in two principal phases by using a sequential process. The qualitative data were collected in the first phase through semi-structured interviews, students’ journal-diaries, document analysis and the open-ended items on the questionnaires. The quantitative data were collected in the second phase through closed-ended questionnaire items. Data were analysed quantitatively by employing the Statistical Package for the Social Sciences (SPSS) descriptive statistics, and qualitatively by utilising exploratory content analysis. The current study’s results demonstrate that the BELC suffers from significant shortcomings which require attention. Deficiencies pertain to the physical environment of the institute site. These encompass antiquated buildings, a restricted amount of classrooms, shortfalls in pedagogic and didactic materials, resources and facilities, and insufficient library accoutrements. In accordance with the study’s conclusions, BELC goals and objectives also show salient concerns which call for reform. The current study’s results also highlight student dissatisfaction with BELC course content and instructional materials and resources; citing uninteresting and unchallenging course topics, as well as obsolete textbooks. The programme’s instructional methodologies were criticised as being too traditionally oriented; the teaching methods as overly lecturer-centred. The study’s outcomes also reveal intense student criticism of the arcane and antiquated assessment philosophy employed by their lecturers. Such evaluative philosophy relies too heavily on one final, course examination which tests only learnt content. The current study contributes to the knowledge of language programme evaluation from various perspectives. It fills a vacuum in the scholarly literature of language programme evaluation, by specifically addressing the Emirati educational context. In addition, the current study contributes theoretically with regard to the social constructivism mode of inquiry in the Emirati context. Finally, the current study proposes an evaluation approach that can be applied, and modified, depending on the specifications of any given setting. "